Climate adaptation in Banke, Nepal: Climate shocks, impacts, responses, and adaptive capacity of local food systems - Chakraborty, Shreya; Banerjee, Anurag; Karki, Saral; Kishore, Avinash; Scott, Samuel P.; Kumar, Neha; Sapkota, Tek; Krupnik, Timothy J.; Menon, Purnima (CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) district agrifood systems assessments aim to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. They are designed to be a district-level multi-year assessments. Using data collected in February–March 2023, this brief describes experiences of climate shocks, perceived impacts and responses, and access to different types of resources that can contribute to the adaptive capacity of households. Here we use the term “climate shocks” to represent manifestations of climatic variability and weather extremes that households perceive and respond to. This is one of a set of data notes that, together, provide a holistic picture of the agrifood system in the district.